Social and economic costs of food allergies in Europe: translation and trans-cultural adaptation into different languages of a questionnaire to measure costs and health utility - Margaret Fox; Inmaculada Cerecedo; Belén de la Hoz Caballer; Javier Zamora; Ewa Rokicka; Pawel Starosta; Nikolaos G. Papadopoulos; Katerina Lagara; Miranda Mugford (University of East Anglia, Health Economics Group (HEG), 2013)
Background: With the growth in international comparative research in the field of health economics, new tools to collect comparative data from disparate countries are required to measure and compare the costs of illnesses. Methods: A multistep approach was used to translate an English questionnaire to measure the costs of food allergies across 12 European countries, using WHO guidelines as a minimum standard. Greek, Polish and Spanish translations are presented as case studies. Survey response rates and item non-response rates were analysed to evaluate the process. Results: Questionnaires were adapted to reflect different health professions and health settings in each country. Spain achieved the highest response rate (85%) and lowest item non-response rate (85%; 1.52%) compared to Poland (68%; 4.97%) and Greece (38%; 10.64%). Spain implemented a more complex translation protocol than Poland and Greece. Conclusion: More complex translation protocols yield better results, but this paper concludes that good channels of communication between originators of questionnaires and translators is most effective way of ensuring good quality outcomes.
Keywords: 330